Preeclampsia: Novel Insights From Global RNA Profiling of Trophoblast Subpopulations. Issue 2 (June 2018) - Gormley, M.; Ona, K.; Kapidzic, M.; Garrido-Gomez, T.; Zdravkovic, T.; Fisher, S.J.
Abstract : ( Am J Obstet Gynecol . 2017;217(2):200.e1–200.e17) Preeclampsia is associated with defects in deep placentation, a characteristic shared with other obstetric syndromes like preterm labor, intrauterine growth restriction, late spontaneous abortion, preterm premature rupture of membranes, and placental abruption. This study used a laser microdissection approach to placentas from severe (and early onset) preeclampsia (sPE) pregnancies to allow for the transcriptional profiling of specific trophoblast subpopulations, including invasive cytotrophoblasts (iCTBs), syncytiotrophoblasts (STBs), and endovascular cytotrophoblasts. Researchers theorized that new insights into the role of these cells in preeclampsia pathogenesis would be revealed using transcriptomic analyses of the trophoblast subpopulations.